Gender Responses to Emotional Appeals in Advertising: Comparing Self-Reports and Facial Expressions - Tsichla, Eirini; Voutsa, Maria C.; Margariti, Kostoula; Hatzithomas, Leonidas (My University, 2021)
Emotional appeals in advertising represent one of the most frequently used creative strategies. Considering that their effectiveness lies on consumers’ subjective reactions to emotions, understanding gender differences in affective responses can form the basis for the development of successful advertising messages. Prior research has highlighted various gender reactions across different emotional appeals in advertising. For instance, women appear to be more receptive towards subtle advertisements that appeal to warmth and affection, while men are more positive towards aggressive, violent and provocative advertisements.
Keywords: Emotional reactions; Advertising stimuli; Expressed emotions; Men; Women